Perancangan Sistem Informasi Jasa Perbaikan AC Berbasis Website Pada perbaikan AC Berbasis Website pada PT. Mitra Teknik Aircond Tangerang - Audy Cesar Ismanto; Yudi Kurniawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
PT. Mitra Teknik Aircond is a company operating in the field of AC and air filters in Indonesia, located in the city of Tangerang, the scope of work includes Design, Procurement, Work and Care/Maintenance of AC and Air Filter Systems. The absence of an information system in managing service sales is an obstacle for companies in selling services, and the lack of media in marketing means that the information obtained by consumers is not optimal. To overcome this, we need an information system that can be accessed by employees to manage sales of their units and also a website application that can be accessed by potential consumers to get information about AC units for sale. For this reason, a web-based home sales information system was developed using Hypertext Preprocessor (PHP), bootstrap framework and MySQL database with the aim of making it easier for employees to carry out AC sales transaction management activities in the process of ordering AC and services by consumers, and also providing convenience. for potential consumers looking for information about AC and services to be purchased from this company. The stages of this research include analysis of the current system, analysis of the proposed system, system design, implementation and testing. PT Aircond Engineering Partner's AC sales information system was tested using the black box method with a success rate of 98% in the process of use by employees or consumers with an easy-to-understand website display.